The Campus Canopy, 1935-04-03 - Georgia State Womans College (Valdosta State University Archives and Special Collections, 1935)
46 Are Placed on Dean's List; Vreeland Presents Brilliant Concert; Glee Club Will Give Concert at Ritz Theater (Valdosta, GA) Theatre Saturday Night; Horseback Riding Class Begins Work; Students in Creative Writing Find Local Color Settings; Patching Tires is Part of the Job for G.S.W.C. Commuters;
Georgia State Womans College. "The Campus Canopy, April 3, 1935." Vol.01, No.13. Valdosta State University Archives and Special Collections, 2018. http://hdl.handle.net/10428/2983. ### Persons Mentioned ### Albert Tuck; Alexa Daley; Annie P. Hopper; Bessie Jo Johnson; Blanche Locklier; Bobbie Cochran; Bootsie Hatcher; Broun Hutchinson; C. C. Varnedoe; C. Whittington; Camille Rycroft; Carol Forrester; Carolyn Askew; Carolyn Greene; Carolyn Whipple; Catherine Mallory; Catherine Morgan; Chappie Bragg; Clara Davis Adams; Clara Louise Driskell; Clare Lawson; Debussy; Dick Powell; Dorothy Ogletree; Edith Bennett; Eleanor Bailey; Elizabeth Sims; Elizabeth Wilkes; Ellie Etheridge; Eloise Ogletree; Emily Fluker; Emma Ambos; Estelle Roberts; Esther Smith; Ethel Adams; Eva Mae Smith; Evelyn May; Florence Tharpe; Floride Zipperer; Floye Ivey; Frances Carson; Frances Crosby; Frances Folsom; Frances McLain; Fred Astaire; Fred MacMurray; Ginger Rogers; Gloria Stuart; Ham Peck; Harold Punke; Heather Angel; Helen Claire; Helen Dale Parrish; Henry L. Smith; Hercules; Herr Hitler; Hulda Summer; Ida Lee Stear; Irene Dunne; Isham Jones; Iva Chandler; Jane Twitty; Jeanette Law; Jeannette Shifrin; Jeannette Vreeland; Jerome Kern; Jesselyn Griggs; Josephine Daniel; Josephine Joubert; Joy Miller; Joyce Tipton; Juanita Sirmans; Judy Cochran; Julia Manning; Katherine Toole; Kathryn Moore; Kitty O'Neal; Forest Smith; Langdon Cheeves; Leila Callendar; Leila Urquhart; Lena Hawkes; Leonora DuFour; Lois Simpson; Lora McPhaul; Louise Hardy; Louise Howell; Louise Sawyer; Lucy Hammond; Lyle Talbot; Margaret Bennett; Margaret Dalton; Margaret Hudson; Margaret Zipplies; Marguerite McCall; Marie Gaskins; Marion Lucas; Marion Reid; Marjorie Groover; Marshall Paulk; Marth Johnston; Martha Franklin; Martha Gardner; Mary Elizabeth Weatherford; Mary Lois Hitch; Mary Polhill; Mary Young Roberts; Maxwell Oliver; Mildred Fokes; Mildred Larsen; Myra Hackett; Nell Greene; Norman Renfroe; Ola Lee Powell; Paris Lee; Pearl Wilson; Permelia Oliff; Rosalie Sutton; Russell McPhail; Ruth Bunn; Ruth Ellis; Ruth Jones; Ruth Williams; Strauss; Susie Mathews; Herman Talmadge; Una Ritch; Viola James; Vivian Stanford; Jeannette Vreeland; W. T. Layson; Wilma Ruth Faircloth; Winnie Davis; Virginia Kirkland; Virginia Zipplies; Ginger Rogers; Wynelle Spell; ### Locations Mentioned ### Adel, Georgia; Albany, Georgia; America; Arlington, Virginia; Atlanta, Georgia; Bainbridge, Georgia; Baxley, Georgia; Cairo, Georgia; Camilla, Georgia; Columbus, Georgia; Cuba; Douglas, Georgia; Dublin, Georgia; Europe; Georgia; Greensboro, South Carolina; Havana, Cuba; Homerville, Georgia; Lake Park, Georgia; Lakeland, Georgia; Leesburg; Lithuania; Milledgeville, Georgia; Nashville, Georgia; New York; Ousley, Georgia; Pembroke, Georgia; Poland; Quitman, Georgia; Ray City, Georgia; Ritz Theater (Valdosta, GA); Sarasota, Florida; Savannah, Georgia; Scotland; Seville, Georgia; South Georgia; Stockton, Georgia; Tallahassee; Valdosta, Georgia; Vienna; Waycross, Georgia; West Hall Rotunda (Valdosta State University); Wrightsville, Georgia; ### Organizations Mentioned ### Athletic Club; Emory University; Fine Arts Club; Florida State College; Georgia State College; Georgia State Womans College; Glee Club; Lambdas; Legion Home; Philharmonic Club; Senior House; U.S. Senate; University System of Georgia;
Keywords: Georgia State Womans College -- Students -- Periodicals; Newspapers; College student newspapers and periodicals -- Georgia -- Valdosta; Women's colleges